solve the equation (x-9) (3 x+1) =0 x= __?
Question
Updated 6/21/2014 10:46:09 AM
This conversation has been flagged as incorrect.
Flagged by yeswey [6/21/2014 10:45:46 AM]
Original conversation
User: solve the equation (x-9) (3 x+1) =0 x= __?

Weegy: Simplifying (x + -9)(3x + 1) = 0 Reorder the terms: (-9 + x)(3x + 1) = 0 Reorder the terms: (-9 + x)(1 + 3x) = 0 Multiply (-9 + x) * (1 + 3x) (-9(1 + 3x) + x(1 + 3x)) = 0 ((1 * -9 + 3x * -9) + x(1 + 3x)) = 0 ((-9 + -27x) + x(1 + 3x)) = 0 (-9 + [ -27x + (1 * x + 3x * x)) = 0 (-9 + -27x + (1x + 3x2)) = 0 Combine like terms: -27x + 1x = -26x (-9 + -26x + 3x2) = 0 Solving -9 + -26x + 3x2 = 0 Solving for variable 'x'. Factor a trinomial. (-1 + -3x)(9 + -1x) = 0 Subproblem 1 Set the factor '(-1 + -3x)' equal to zero and attempt to solve: Simplifying -1 + -3x = 0 Solving -1 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -3x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -3x = 0 + 1 -3x = 0 + 1 Combine like terms: 0 + 1 = 1 -3x = 1 Divide each side by '-3'. x = -0.3333333333 Simplifying x = -0.3333333333 Subproblem 2 Set the factor '(9 + -1x)' equal to zero and attempt to solve: Simplifying 9 + -1x = 0 Solving 9 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -1x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -1x = 0 + -9 -1x = 0 + -9 Combine like terms: 0 + -9 = -9 -1x = -9 Divide each side by '-1'. x = 9 Simplifying x = 9 Solution x = {-0.3333333333, 9} ]
Marvel2|Points 1185|

User: solve the equation 4x(x+4) =0 x=___?

Weegy: Simplifying 4 + x = 0 Solving 4 + x = 0 Move all terms containing x to the left, [ all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + x = 0 + -4 x = 0 + -4 Combine like terms: 0 + -4 = -4 x = -4 Simplifying x = -4 ]

Question
Updated 6/21/2014 10:46:09 AM
This conversation has been flagged as incorrect.
Flagged by yeswey [6/21/2014 10:45:46 AM]
Rating
3
(x - 9) (3x + 1) = 0
x - 9 = 0 or 3x + 1 = 0
x = 9 or x = -1/3
Confirmed by andrewpallarca [6/21/2014 10:48:28 AM]
3
4x(x + 4) = 0
x = 0 or x + 4 = 0
x = 0 or x = -4
Confirmed by andrewpallarca [6/21/2014 10:48:49 AM]

27,365,761
*
Get answers from Weegy and a team of really smart live experts.
Popular Conversations
The Monroe Doctrine was updated and adapted to the Roosevelt era with ...
Weegy: The Monroe Doctrine was updated and adapted to the Roosevelt era with The Roosevelt Corollary. User: Which ...
______ is a literary tool that suggests mental pictures of sights, ...
Weegy: Simile is a figure of speech in which two unlike things are explicitly compared. User: "The fog comes On ...
what is medical control
Weegy: Medical billing is basically an interactive process between registered medical institutions, medical ...
Irrational number
Weegy: Integers are NEVER irrational numbers. User: Integers
Mongol conquerors founded which Chinese Dynasty?
Weegy: The Mongols, or Mongolic peoples, are a Central and Northern Asian (Inner Asia) ethno-linguistic group. User: ...
S
L
Points 1243 [Total 1554] Ratings 15 Comments 1093 Invitations 0 Offline
S
L
R
P
R
P
R
P
R
Points 451 [Total 1226] Ratings 3 Comments 391 Invitations 3 Offline
S
R
L
R
P
R
P
R
R
R
R
Points 448 [Total 1332] Ratings 4 Comments 318 Invitations 9 Offline
S
L
P
P
P
Points 356 [Total 1232] Ratings 0 Comments 356 Invitations 0 Offline
S
L
R
Points 75 [Total 192] Ratings 0 Comments 75 Invitations 0 Offline
S
Points 33 [Total 33] Ratings 1 Comments 23 Invitations 0 Offline
S
Points 23 [Total 23] Ratings 0 Comments 23 Invitations 0 Offline
S
Points 12 [Total 12] Ratings 0 Comments 2 Invitations 1 Offline
S
Points 10 [Total 10] Ratings 0 Comments 0 Invitations 1 Offline
S
L
1
R
Points 2 [Total 1453] Ratings 0 Comments 2 Invitations 0 Offline
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.